Ghost-ileostomy versus conventional loop ileostomy in patients undergoing low anterior resection for rectal cancer: results of a randomised controlled multicentre pilot trial (DRKS00013997) - Hüttner, Felix; Probst, Pascal; Mihaljevic, André L.; Sauer, Lukas; Dörr-Harim, Colette; Ulrich, Alexis; Stratmeyer, Samira; Klotz, Rosa; Diener, Markus K.; Knebel, Phillip (Langenbeck's archives of surgery, 2024)
The objective of the current pilot trial was to evaluate whether ghost ileostomy is a safe alternative to the current standard of care in terms of a conventional loop ileostomy in patients undergoing low anterior resection with total mesorectal excision (LAR/TME) for rectal cancer.